11 - Why France Can’t Be Nigeria’s Strategic Partner - Yusuf Bangura (CODESRIA Bulletin, 2025)
I’ve seen and listened to many responses – some direct, others indirect – to my article on the problems of Nigeria’s foreign policy, which looked at Nigeria’s assigned role in BRICS as a ‘partner member’ and its new-found love of France. That article has been widely circulated on Facebook and WhatsApp as well as in a number of online Nigerian newspapers, including Premium Times, Daily Trust and Intervention. It portrays Nigeria’s decision to join BRICS as a partner member as an indication of its declining role in world afairs and its pursuit of a transactional approach in the conduct of its foreign policy. It also questions Nigeria’s full embrace of France (a historical rival) as a regional partner at a time when hatred for French neocolonial policies in Francophone Africa is at an all- time high. Two articles, one by Muhammad Al-Ghazali (in Daily Trust)2 and another by Toba Alabi (in Future World), a professor of political science and defence studies at the Nigerian Defence Academy, fully supported my arguments. Bolaji Akinyemi, the doyen of Nigerian foreign policy, also questioned Nigeria’s partner member status in BRICS in an interview he gave on Channels TV on Trump’s inaugural lecture.